2019
DOI: 10.1002/ijc.32426
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and risk of liver cancer: Evidence from two population‐based studies

Abstract: Epidemiological studies of statin use and liver cancer risk have produced conflicting results. We examined the association between statin use and risk of primary liver cancer in two large independent study populations taking account of important covariates and main indications of statins such as high cholesterol and chronic liver disease. We performed a nested case–control study within the Scottish Primary Care Clinical Informatics Unit (PCCIU) database. Five controls were matched to cases with primary liver c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 31 publications
(55 reference statements)
2
66
0
Order By: Relevance
“…Nine studies [8,10,[12][13][14]18,20,22] were retrospective case-control, twelve were cohort studies [9,11,[15][16][17]19,23,24,26,27,29,30], one study was a randomized controlled trial (RCT) [28], and two studies that were included as RCTs represented individual patient data analysis of patients enrolled in prospective controlled trials of cholesterol in heart disease [31,32]. The study by Tran et al [25] included two different stages, a nested case-control and a prospective cohort drawn from two different populations, hence they were analyzed separately.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Nine studies [8,10,[12][13][14]18,20,22] were retrospective case-control, twelve were cohort studies [9,11,[15][16][17]19,23,24,26,27,29,30], one study was a randomized controlled trial (RCT) [28], and two studies that were included as RCTs represented individual patient data analysis of patients enrolled in prospective controlled trials of cholesterol in heart disease [31,32]. The study by Tran et al [25] included two different stages, a nested case-control and a prospective cohort drawn from two different populations, hence they were analyzed separately.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Tran et al ( 27 ) found that taking lipid‐lowering agent was associated with the risk of liver cancer. Therefore, to further eliminate the interference of potential confounders on the results, sensitivity analysis and subgroup analysis were conducted, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…8 Statins may also lower the risk of liver cancer. 9 The anti-inflammatory effects vary among the different types of currently licensed statins with various meta-analyses reporting differential efficacy in reducing inflammation in chronic obstructive pulmonary disease (COPD). 10 Statins (table 1) are categorised into two main groups according to their solubility: (1) hydrophilic statins which include pravastatin and rosuvastatin and these display high hepato-selectivity with increased first-pass effect and (2) lipophilic statins which are characterised by passive diffusion into cells; these include atorvastatin, simvastatin, lovastatin, fluvastatin, pitavastatin and cerivastatin.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%